Training On The Use Of The Book “Balanced Nutrition Of Youth: Prevent Stunting” To Improve Adolescent Food Consumption Patterns: Pelatihan Pemanfaatan Buku “Gizi Seimbang Remaja: Cegah Stunting” Untuk Meningkatkan Pola Konsumsi Pangan Remaja - Aslis Wirda Hayati; Husnan Husnan; Roziana Roziana (Jurnal Pengabdian Kesehatan Komunitas, 2022)
The prevalence of stunting in the Southeast Asia/South-East Asia Regional (SEAR) is 36.4%. One of the efforts to prevent and reduce the prevalence of stunting is to teach teenagers about food consumption patterns based on balanced nutrition. This community service aims to improve adolescent food consumption patterns. This training is conducted from February to February. August 2022. Dietary counseling was conducted 3 times using the book "Balanced Nutrition for Youth: Prevent Stunting" at SMP N 1 Kampar, Kampar District, Kampar Regency. Assessment of adolescent eating patterns was carried out using pre and post test questionnaires. Questions related to the type, amount and frequency of eating. The practice of administering food was carried out 3 times at the Food Processing Laboratory of the Integrated Laboratory of Poltekkes, Ministry of Health, Riau on Jl. Melur 103 Pekanbaru City. Assessment of adolescent skills in food administration was carried out by observing using a checklist. The number of participants in the training was 12 teenagers. The result of this activity is an increase in adolescent food consumption patterns by 6.7%, from 82.7 to 89.4%. The increase in value is seen in the frequency of food consumption, from 75 to 80%. The type and amount of food consumed by adolescents since before the training seems to have been good with a value above 80%. The average balanced menu processing practice by adolescents is in the good category with a score above 80%. The conclusion of this activity is that there is an increase in adolescent food consumption patterns after participating in the Training on the Use of the Book "Balanced Nutrition for Adolescents: Prevent Stunting". The type and amount of food consumed by adolescents was good since before the training. The frequency of adolescent food consumption became good after the training. Abstrak Prevalensi stunting di regional Asia Tenggara/South-East Asia Regional (SEAR) yaitu sebesar 36,4%. Salah satu upaya untuk mencegah dan mengurangi prevalensi stunting yaitu mengajarkan kepada remaja tentang pola konsumsi pangan berdasarkan gizi seimbang. Pengabdian kepada masyarakat ini bertujuan meningkatkan pola konsumsi pangan remaja. Pelatihan ini dilakukan bulan Februari s.d. Agustus 2022. Penyuluhan pola makan dilakukan sebanyak 3 kali dengan menggunakan Buku “Gizi Seimbang Remaja: Cegah Stunting” di SMP N 1 Kampar Kecamatan Kampar Kabupaten Kampar. Penilaian pola makan remaja dilakukan menggunakan kuesioner pre dan post test. Pertanyaan berkaitan dengan jenis, jumlah dan frekuensi makan.  Praktik penyelenggaraan makanan dilakukan sebanyak 3 kali di Laboratorium Pengolahan Pangan Laboratorium Terpadu Poltekkes Kemenkes Riau di Jl. Melur 103 Kota Pekanbaru. Penilaian keterampilan remaja dalam penyelenggaraan makanan dilakukan dengan observasi menggunakan daftar tilik. Jumlah peserta pelatihan sebanyak 12 orang remaja. Hasil dari kegiatan ini yaitu terjadi peningkatan pola konsumsi pangan remaja sebanyak 6,7% yaitu dari 82,7 menjadi 89,4%. Peningkatan nilai terlihat pada frekuensi konsumsi pangan yaitu dari 75 mejadi 80%. Jenis dan jumlah pangan yang dikonsumsi remaja sejak sebelum pelatihan terlihat sudah baik dengan nilai di atas 80%. Rata-rata praktik pengolahan menu seimbang oleh remaja sudah termasuk kategori baik dengan nilai di atas 80%.  Kesimpulan dari kegiatan ini yaitu terjadi peningkatan pola konsumsi pangan remaja setelah mengikuti kegiatan Pelatihan Pemanfaatan Buku “Gizi Seimbang Remaja: Cegah Stunting”.  Jenis dan jumlah pangan yang dikonsumsi remaja sudah baik sejak sebelum pelatihan.  Adapun frekuensi konsumsi pangan remaja menjadi baik setelah pelatihan.